Optimal allocation of dynamic VAR sources using zoning-based distributed optimization algorithm. (December 2019) - Mao, Xiaoming; Zhu, Weifeng; Wu, Liang; Zhou, Baorong
Highlights: A systematic planning method to allocate dynamic VAR sources is proposed. The concept of voltage control area is proposed to partition a bulk power system. A zone-based voltage supporting index is defined in the site selection process. A zone-based distributed optimization framework is put forward. Abstract: In this paper, a practical planning method to allocate dynamic VAR sources (DVSs) using the concept of voltage control areas (VCAs) is proposed to enhance short-term voltage stability of power systems. Firstly, based on the defined transient distance index, a spectral clustering method is employed to partition a system into VCAs. Then, candidate DVS sites in each zone are determined by the proposed voltage supporting index. In each VCA, the capacity of candidate sites is preliminarily estimated by use of the dichotomy method to decide the most effective control bus and the initial capacity guess, based on which further system-wide optimization is implemented using particle swarm optimization (PSO) to obtain the final allocation scheme. Case study on the New England 39-bus and 68-bus test systems along with the comparisons with the existing methods confirm the effectiveness and advantages of the proposed methodology.